PENINGKATAN PERAN WANITA TERHADAP PENANGGULANGAN BENCANA BANJIR DI KAWASAN RAWAN BENCANA BANJIR KABUPATEN SERANG - Mudmainah Vitasari; Fuja Siti Fujiawati (Universitas Sebelas Maret (UNS), 2018)
Floods are an inevitable event for countries with tropical climates such as Indonesia. Floods can hit anything and everything in the flood-prone areas that allow the emergence of disasters in the form of material losses and casualties. Women who belong to the